Urinary Uromodulin Levels and UMOD Variants in Black South Africans with Hypertension-Attributed Chronic Kidney Disease - Nolubabalo Unati Nqebelele; Caroline Dickens; Therese Dix-Peek; Raquel Duarte; Saraladevi Naicker (International Journal of Nephrology)
Uromodulin, the most abundant protein in urine, is synthesized in the thick ascending loop of Henle and distal convoluted tubules. Patients with chronic kidney disease (CKD) have reduced urinary uromodulin levels secondary to tubular damage. Genome wide association studies identified significant single nucleotide polymorphism (SNP) associations with CKD at the uromodulin (UMOD) locus. We examined the association of urinary uromodulin concentrations with CKD and with SNP rs1333226 in the UMOD gene. The study included 71 black South Africans with hypertension-attributed CKD with an eGFR ≤ 60ml/min/1.73m2, 52 first-degree relatives, and 58 unrelated controls. Urinary uromodulin concentration was measured using Luminex® multiplex kits. After DNA extraction from blood using the Maxwell® automated platform, genotyping of rs13333226 was performed using real-time PCR using TaqMan® genotyping assays. Urinary uromodulin levels were significantly lower in CKD cases compared to both controls and first-degree relatives and correlated negatively with age, serum uric acid, serum creatinine, and systolic BP and positively with CKD-EPI eGFR. For each 1-standard deviation increase in uromodulin level, the multivariable-adjusted odds ratio for CKD was 0.6 (95% CI [0.48 to 0.81]; p <0.01). There were no significant differences in the minor allele frequency between CKD cases and controls (p = 0.59) nor between first-degree relatives and controls (p = 0.98). There were no significant associations between genotype at rs13333226 and urine uromodulin levels (p = 0.43). Higher levels of urinary uromodulin are associated with lower odds of hypertension-attributed CKD. We did not detect associations of genotype at rs13333226 with urinary uromodulin levels in our sample population. Larger sample size studies from ethnically disparate populations are essential to further categorize this association.